Microelectronic transmitter of optical power density on the basis of silicon solar elements - Osadchuk, V. S.; Osadchuk, O. V.; Ilchenko, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The mathematical model of the microelectronic optical power density transducer on the basis of field-effect transistors and silicon solar cell is developed. Analytical dependences for the conversion function and sensitivity equation are received on the basis of the model.